ChemInform Abstract: Reductive Transformation of CO2 with Hydrosilanes Catalyzed by Simple Fluoride and Carbonate Salts. Issue 12 (March 2016) - Motokura, Ken; Naijo, Masaki; Yamaguchi, Sho; Miyaji, Akimitsu; Baba, Toshihide
Abstract: The method is suitable for the synthesis of silyl formate and formamide derivatives.